The Farnsworth-Munsell 100 hue test in the first episode of demyelinating optic neuritis. Issue 2 (February 1993) - Ménage, M J; Papakostopoulos, D; Dean Hart, J C; Papakostopoulos, S; Gogolitsyn, Y
Abstract : The Farnsworth-Munsell 100 hue test (F-M 100) was used to examine 30 patients with their first episode of unilateral demyelinating optic neuritis (DON) at presentation, after 6 weeks and after 6 months. Twelve patients satisfactorily completed the test with the affected eye at presentation. This number had increased to 23 by 6 weeks and to 27 by 6 months. No patient with a visual acuity of LogMAR 0.86 (Snellen equivalent approx 6/43) or worse, could complete the test. The mean total error score of affected eyes showed significant improvement at each subsequent examination but was always worse than the non-affected eyes. There was a significant correlation between total error scores and visual acuities of affected eyes at presentation and after 6 months. Fourteen patients recovered a visual acuity of LogMAR 0.0 (Snellen equivalent 6/6) or better but the total error scores of the affected eyes were significantly worse than the non-affected eyes (p = 0.017), indicating that defective colour vision is an indicator of a previous episode of DON despite the recovery of normal visual acuity. DON is reported to produce a red-green (Type II) axis of colour defect but individual F-M 100 polar diagrams were usually generally abnormal and did not show any predominance of recognisable axis of colour defect at any examination. Group averaging of the F-M 100 data from such a well-defined group of patients with acute DON revealed a significant bipolar abnormality in the tritan (blue-yellow) axis at presentation which was not demonstrated at the subsequent examinations or at any examination of the non-affected eyes.